2014
DOI: 10.7759/cureus.182
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Adipose-derived Stromal Stem Cell Implantation to Resolve Critical Limb Ischemia: Case Report

Abstract: Critical limb ischemia (CLI) is a debilitating condition for which limited therapeutic options exist. Characterized by ischemia of the lower limb due to vascular deficiency, attempts have been made to stimulate angiogenesis utilizing cell and gene-based approaches. Adipose stromal vascular fraction (SVF) cells are a practical source of autologous tissue that can be prepared inexpensively in a same-day procedure. Recent studies have demonstrated SVF to be highly angiogenic, as well as clinically safe in a varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“… 13 This cluster of differentiation is part of the periendothelial network and is thought to be integral to the angiogenesis process. The use of SVF has been reported in a variety of indications including osteoarthritis, 14 – 16 degenerative disc disease, 17 sclerosis, 18 tendinopathy, 19 congestive heart failure, 20 chronic obstructive pulmonary disease, 21 radiation necrosis, 22 xerostomia, 23 and multiple sclerosis. 24 In addition, two studies have been published demonstrating the safety of SVF for a variety of indications used in a clinical outpatient setting.…”
Section: Introductionmentioning
confidence: 99%
“… 13 This cluster of differentiation is part of the periendothelial network and is thought to be integral to the angiogenesis process. The use of SVF has been reported in a variety of indications including osteoarthritis, 14 – 16 degenerative disc disease, 17 sclerosis, 18 tendinopathy, 19 congestive heart failure, 20 chronic obstructive pulmonary disease, 21 radiation necrosis, 22 xerostomia, 23 and multiple sclerosis. 24 In addition, two studies have been published demonstrating the safety of SVF for a variety of indications used in a clinical outpatient setting.…”
Section: Introductionmentioning
confidence: 99%
“…SVF includes a cell population with greater than 50% CD34 expression and high viability (> 90%). The ADSCs isolated can also differentiate in culture into fat, bone and cartilage [27].…”
Section: Collection Of Adipose Tissue and Cell Populationmentioning
confidence: 99%
“…Fat tissue can be easily and safely harvested and SVF can be collected bedside making it an attractive therapeutic option for physicians to offer to their patients [19]. A variety of publications have reported on the injection of SVF including: osteoarthritis [20, -21], degenerative disc disease [22], sclerosis [23], tendinopathy [24], congestive heart failure [25], chronic obstructive pulmonary disease (COPD) [26], radiation necrosis [27], xerostomia [28], psoriasis [29], and multiple sclerosis [30].…”
Section: Introductionmentioning
confidence: 99%
“…Comella et al reported on the safety of SVF in a variety of indications with various delivery methods. Other publications have demonstrated success of SVF for specific conditions including: chronic obstructive pulmonary disease (COPD) [17], congestive heart failure [18], degenerative disc disease [19], osteoarthritis/orthopedics [20][21][22][23][24], radiation necrosis [25], sclerosis [26], tendinopathy [27], xerostomia [28], psoriasis [29] and multiple sclerosis [30]. The following is a case report and to our knowledge first in man a single injection of SVF and PRP into a chronic non-healing stage 3 ulcer in a patient with an incomplete spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%